2019
DOI: 10.1097/acm.0000000000002654
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Training Program to Diversify the Biomedical Research Workforce

Abstract: The National Institutes of Health has made considerable investments to diversify the biomedical research workforce. Towards this goal, the authors partnered with representatives from several minority-serving institutions (MSIs) to develop training for the next generation of researchers. To ensure the most effective training program, the authors conducted a needs assessment with junior and senior investigators from the partnering MSIs. In 2016, the authors conducted focus groups and interviews with 23 junior in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…Nonformal, interprofessional curricular structures support underrepresented students by offering a flexible and responsive environment for enhancing the biomedical research training of undergraduates. These findings are consistent with those from undergraduate and faculty STEM development programs that implement peer-enhanced supplemental instruction (Merolla & Serpe, 2013;Rubio et al, 2019;Toven-Lindsey et al, 2015). Enrichment engages diverse students in peer spaces and facilitates activities that give them a sense of ownership over the development of their professional identities, as well as practical tools to succeed in the academic and professional path of their choosing, on their own terms.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Nonformal, interprofessional curricular structures support underrepresented students by offering a flexible and responsive environment for enhancing the biomedical research training of undergraduates. These findings are consistent with those from undergraduate and faculty STEM development programs that implement peer-enhanced supplemental instruction (Merolla & Serpe, 2013;Rubio et al, 2019;Toven-Lindsey et al, 2015). Enrichment engages diverse students in peer spaces and facilitates activities that give them a sense of ownership over the development of their professional identities, as well as practical tools to succeed in the academic and professional path of their choosing, on their own terms.…”
Section: Discussionsupporting
confidence: 81%
“…Sites reported that their students consistently self-identified imposter syndrome as a problem, even as they gained research experience and credentials, including first-author publications. Our observations underscore a need to explicitly address hidden and implicit curricula with undergraduates as part of biomedical research training, which was also identified as a need for professional development training by both junior and senior biomedical faculty (Rubio et al, 2019) as well as undergraduate programs (Hinton et al, 2020;Merolla & Serpe, 2013;Toven-Lindsey, Levis-Fitzgerald, Barber, & Hasson, 2015). Together, these findings highlight a common need for instruction across all biomedical training levels.…”
Section: Enrichment Surfaces Implicit Curriculasupporting
confidence: 53%
“…Creating effective career development programs is instrumental for intensive research institutions to accelerate the research careers of researchers. Models for junior investigators' career success include critical components, such as self-awareness, selecting the right topic, adequate support, working with others, and managing themselves (12). Moreover, mentored research training during doctoral training leads to an increased likelihood of developing a research career (13).…”
Section: Initial Evidence Of Impactmentioning
confidence: 99%
“…LEADS focused on developing the skill set of early career investigators while simultaneously providing mentoring and coaching from trained senior faculty, as well as resources that allowed them to partake in research dissemination, networking opportunities, and additional training. In another paper, we describe LEADS in detail [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The LEADS program has been described in detail elsewhere [ 9 ]. One particular aspect deserves additional focus, however: LEADS’ coaching and mentoring components.…”
Section: Introductionmentioning
confidence: 99%